Spiritual Support Improves Quality of Life in Diabetes Mellitus Patients - Mulyana, Mulyana; Priasmoro, Dian Pitaloka; Kurniawan, Ardhiles Wahyu (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Patients with diabetes often experience a decline in their quality of life. Among the various indicators used to assess quality of life, spirituality has garnered increased attention. This emphasis is due to the recognition that spiritual support is a vital component of human well-being, as it embodies an individual's pursuit of meaning and purpose while nurturing a connection with a higher power. This study aimed to investigate the correlation between spiritual support and quality of life among patients with diabetes mellitus at the Wonokerto Health Center in Malang Regency. A correlational study design was employed, utilizing purposive sampling to recruit 64 participants from the health centre's service area. Data collection occurred between October 3 and October 27, 2024. The research instruments utilized included the Daily Spiritual Experience Scale (DSES) and the World Health Organization Quality of Life-BREF (WHOQOL-BREF). The findings indicated that a majority of diabetes mellitus patients (53 respondents, 82.81%) reported high levels of spiritual support, while a significant portion (44 respondents, 68.75%) indicated an excellent quality of life. Data analysis using the Somers' D and Gamma tests revealed a p-value of 0.016 (p < 0.05), suggesting a statistically significant relationship between spiritual support and quality of life in individuals with diabetes. The correlation index (r = 0.546) showed a moderate strength of association, suggesting that heightened spiritual support is correlated with an improved quality of life for patients with diabetes mellitus. In conclusion, spiritual support for patients with diabetes mellitus must be consistently fostered to enhance their quality of life and facilitate more effective coping strategies for managing their condition.